Fungal diseases of Rose plant in Bangladesh (Journal of Bangladesh Academy of Sciences, 2014)
Five types of symptom were recorded on two varieties of rose plant. The symptoms were Black spot, Leaf spot1, Leaf spot2, Blight and Anthracnose. The study revealed the presence of 20 species of fungi belonging to 17 genera. The isolated fungi were Alternaria alternata (Fr.) Keissler, Arthrinium saccharicola Stevenson, Aspergillus flavus, Link., A. niger van Tiegh., Botrytis allii Munn, Cercospora sp., Cladosporium cladosporioides (Fresen.) de Vries, C. oxysporum Berk. & Curt., two species of Colletotrichum, Curvularia brakyospora Boedijn, Curvularia pallescens Boedijn, Fusarium sp., Epicoccum purpurascens Ehreneb ex Schlecht; Link, Gibberella sp., Marssonina rosea (Lib.) Died, Nigrospora sphaerica (Sacc.) Masson, Pestalotiopsis guepinii (Desm.) Stay. with its two culture types, Penicillium sp., Rhizopus stolonifer (Ehrenb. Ex. Fr) Vuill. and Trichoderma viride Pers. ex Fries. The frequency (%) of association of P. guepinii was higher than any other fungi. Pestalotiopsis guepinii and its two culture types were found to be pathogenic to rose plant. DOI: http://dx.doi.org/10.3329/jbas.v38i2.21347 Journal of Bangladesh Academy of Sciences, Vol. 38, No. 2, 225-233, 2014